Visualizing liquid distribution across hyphal networks with cellular resolution - Clark,AJ; Masters-Clark,E; Moratto,E; Junier,P; Stanley,CE (Biomicrofluidics, 2024)
Filamentous fungi and fungal-like organisms contribute to a wide range of important ecosystem functions. Evidence has shown the movement of liquid across mycelial networks in unsaturated environments, such as soil. However, tools to investigate liquid movement along hyphae at the level of the single cell are still lacking. Microfluidic devices permit the study of fungal and fungal-like organisms with cellular resolution as they can confine hyphae to a single optical plane, which is compatible with microscopy imaging over longer timescales and allows for precise control of the microchannel environment. The aim of this study was to develop a method that enables the visualization and quantification of liquid movement on hyphae of fungal and fungal-like microorganisms. For this, the fungal–fungal interaction microfluidic device was modified to allow for the maintenance of unsaturated microchannel conditions. Fluorescein-containing growth medium solidified with agar was used to track liquid transported by hyphae via fluorescence microscopy. Our key findings highlight the suitability of this novel methodology for the visualization of liquid movement by hyphae over varying time scales and the ability to quantify the movement of liquid along hyphae. Furthermore, we showed that at the cellular level, extracellular movement of liquid along hyphae can be bidirectional and highly dynamic, uncovering a possible link between liquid movement and hyphal growth characteristics. We envisage that this method can be applied to facilitate future research probing the parameters contributing to hyphal liquid movement and is an essential step for studying the phenomenon of fungal highways.